Efektivitas Pembelajaran Matematika Menggunakan Media Berbasis E-Learning - Lutfiyah Lutfiyah; Dwi Noviani Sulisawati (Jurnal Pendidikan Matematika:Judika Education, 2019)
The purpose of this study is to see the effectiveness of the use of e-learning based media in mathematics learning at the Raudlatuth Thalabah Vocational School. Research methods, namely quantitative research with descriptive research designs where data collection uses the test, observation, and questionnaire methods. Data analysis was performed descriptively quantitatively involving 25 students of class X-A. The results of the research and analysis of the data obtained obtained information that each aspect of the ability to manage the learning process, and student activities during learning, learning outcomes of students and the responses students have after participating in learning are good criteria. It can be concluded that mathematics learning using e-learning based media is significantly effective. Keywords: Effectiveness, E-learning Media, Mathematics Learning